The thermal structure of small and shallow Arctic Fennoscandian lakes - Mingzhen Zhang; Matti Leppäranta; Maija Heikkilä; Kaarina Weckström; Atte Korhola; Nina Kirchner; Annika Granebeck; Frederik Schenk; Jan Weckström (Arctic, Antarctic, and Alpine Research)
A continuous three-year field study, focusing on the thermal regime and the heat budget of twelve shallow Arctic lakes in northwest Finland, was conducted between 2019 and 2022. The results reveal diverse thermal regimes among these lakes, ranging from cold monomictic to discontinuous cold polymictic and dimictic patterns, reflecting the unique lake responses to their environmental settings. The heat budget of these lakes was predominantly influenced by the strong seasonality of the radiation balance, with latent and sensible heat fluxes consistently exhibiting negative values during the ice-free period, peaking in the summer or late fall. Air temperature and solar radiation were the primary drivers affecting lake thermal structures, at both local and regional scales. The influence of wind speed and cloudiness was more significant for lakes in the treeless tundra, but their regional impact remains relatively weak, along with the impact of precipitation. Additionally, we emphasize the critical role of lake location, geography, and morphology, and particularly altitude, lake size, and water column transparency, in determining changes in stratification and mixing dynamics, overshadowing the influence of lake depth. In conclusion, this study provides new insights into the evolving thermal dynamics of lakes in the European Arctic.